Você está na página 1de 1

1

0

z

0

x+z

0

6xzdydxdz

0

0

π/2

0

3

1

1z 2

0

ze y dxdzdy

y

0

x cos(x + y + z)dzdxdy

0

E 2xdV E = {(x, y, z)|0 y 2, 0 x 4 y 2 , 0 z y}

E 6xydV E z = 1 + x + y

xy y = x y = 0 x = 1

E x 2 e y dV E z = 1 y 2

z = 0 x = 1 x = 1

T x 2 dV T (0, 0, 0) (1, 0, 0) (0, 1, 0)

(0, 0, 1)

T x 2 dV T (0, 0, 0) (2, 0, 0) (0, 3, 0)

(0, 0, 1/2)

E xdV E x = 4y 2 + 4z 2 x = 4

0 x 1 0 y 1 0 z 5 x 2 3y 2

x 2 + y 2 z 4

x 2 z 1 y y 0

1

3 (e 3 1)

8π

8

3e

16π/3